Up-to-date potential of antithrombotic therapy in patients with coronary artery disease and diabetes - O. D. Ostroumova; A. I. Kochetkov; A. A. Kirichenko; M. V. Klepikova; O. V. Golovina; I. A. Alyautdinova (Российский кардиологический журнал)
Almost half of patients with coronary artery disease (CAD) have concomitant diabetes, and this, in turn, significantly increases cardiovascular risk. Modern approaches to the treatment of patients with CAD and comorbid diabetes are aimed at reducing cardiovascular risk, and acetylsalicylic acid remains the basis of antithrombotic therapy for such patients. Combined therapy with rivaroxaban and acetylsalicylic acid reduces risk of significant events in different categories of patients. The safety profile of dual antithrombotic therapy remains invariably optimal, regardless of comorbidities.